Digital Twin Budgeting in Healthcare Fund Oversight: Financial Modeling for Multi-Stakeholder Development Initiatives - Nnadozie Odinaka,; Chinelo Harriet Okolo,; Onyeka Kelvin Chima,; Oluwatobi Opeyemi Adeyelu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The integration of digital twin technology into healthcare budgeting and fund oversight has emerged as a transformative approach to optimize resource allocation and promote transparency. This paper explores the application of digital twin financial modeling in managing multi-stakeholder healthcare development initiatives, particularly those funded by bilateral and multilateral donors. Using a combination of simulation-based modeling, stakeholder alignment matrices, and predictive analytics, the study establishes a framework for real-time budget oversight, anomaly detection, and strategic fund distribution. The findings reveal that digital twin budgeting can significantly enhance governance mechanisms by offering continuous insight into financial performance, identifying leakage patterns, and facilitating compliance reporting. The study contributes to the literature on health systems financing by offering a practical model for digital transformation in fund stewardship, especially within low- and middle-income country (LMIC) contexts.
Keywords: Healthcare budgeting; digital twin; fund oversight; financial modeling; donor initiatives; health governance